Pengaruh Keterbukaan Perdagangan dan Penanaman Modal Asing terhadap Pertumbuhan Ekonomi Anggota G20 - Lelya Dwi Damayanti; Hendry Cahyono (Jurnal Ekonomika : INDEPENDEN, 2025)
The purpose of this study is to analyze the impact of trade openness and foreign direct investment (FDI) on the economic growth of G20 member countries from 1999 to 2023. Additionally, technological advancement is also considered as a supporting variable in this analysis. The method used is a quantitative approach utilizing secondary data obtained from the World Bank. Based on the analysis, trade openness has a significant negative effect on economic growth. Meanwhile, foreign direct investment and technological advancement show a significant positive impact on economic growth. It can be concluded that economic openness can have varying effects on economic growth depending on the specific conditions of each country.